Maternal Periodontitis and Neonatal Inflammation: A Prospective Cohort Study - Parthiban, S.; Arbaaz, B.Roshan; suresh, Snophia; Sophia, Khumukcham; R, kadhiresan.; Ahamed, A.Nihal (Journal of Neonatal Surgery, 2025)
Background: Periodontitis has been linked to adverse pregnancy outcomes , but its impact on neonatal inflammation remains unclear. Objective: To investigate the relationship between maternal periodontitis and neonatal inflammation . Methods: A prospective cohort study was conducted among pregnant women with periodontitis and healthy controls. Maternal periodontal status was assessed, and neonatal cord blood was analyzed for inflammatory markers (IL-6 and TNF-α). Results: Maternal periodontitis was associated with increased neonatal inflammatory markers (IL-6 and TNF-α) and lower birth weight. A positive correlation was found between maternal periodontal disease severity and neonatal inflammatory markers. Conclusion: Maternal periodontitis is associated with increased neonatal inflammation , suggesting a potential link between maternal oral health and fetal development. These findings highlight the importance of prenatal periodontal care in reducing adverse birth outcomes.